THE EFFECT OF PAPAYA LEAF EXTRACT (Carica papaya) AND ZEOLITE ON WATER QUALITY IN THE CULTIVATION MEDIUM FOR STRIPED CATFISH (Pangasianodon hypophthalmus) - Dhearesta, Anugrah Aurora; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Striped catfish maintenance media often experience water quality problems. Efforts to overcome water quality problems can be made using papaya leaves (Carica papaya). Papaya leaf has benefits in maintaining water quality. In addition to papaya leaf, zeolite can be added as a water filter in the maintenance media. One of the water quality parameters that must be maintained is the physical parameters, namely temperature, turbidity, DHL, TDS, and TSS. This research was conducted from April 2024 to February 2025. This study aimed to determine the effect and best dosage of papaya leaf and zeolite solutions on water quality in striped catfish seed cultivation media. The method used in this study was the experimental method and Completely Randomized Design (CRD), which used four treatment levels with three replications. The treatments given were without papaya leaf solution and zeolite (P0), papaya leaf solution 4 mL/L and zeolite 17.05 g/L (P1), 5 mL/L and zeolite 17.05 g/L (P2), 6 mL/L and zeolite 17.05 g/L (P3). The striped catfish used was 5.9-6.6 cm in size, with a stocking density of 60 fish/tank. Fish maintenance was carried out for 30 days, with feeding conducted at satiation levels, and the feeding frequency was 3 times a day, namely 08:00 WIB, 13:00 WIB, and 16:00 WIB. The administration of 6 ml/L papaya leaf solution resulted in temperature (25.63±0.05b), turbidity (1.83±0.01a), electrical conductivity (83.66±0.57a), TDS (63.66±0.57a) and TSS (28.00±1.00a) and absolute weight of 2.92±0.313c g/fish, absolute length of 3.56±0.472b cm/fish and LPS value of 1.72±0.122c g/day. Papaya leaf solution and zeolite filter significantly affected water quality.